(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article considers the role of mass media in the process of socialization and formation of society value orientations. All changes in value orientations and in state ideology are refl ected in mass media activity. According to the majority of the authors that evaluate the impact of mass media on contemporary society, there are negative moments prevailing in mass media practice concerning socialization as well as forming positive traditional value orientations. These negative moments are connected to the actual self-elimination of the state from the sphere of regulation of activity of mass media. Negative impact of contemporary mass media is about manipulating with mass consciousness by means of the spreadaround standards of behaviour controlling and transforming the inner, spiritual world of a person. The current situation generates the ambiguity of mass media assessment. On the one hand, mass communication and mass media development positively infl uences awareness of individuals of the world around them, but in the same time there is one factor of manipulating with mass consciousness, that stands behind this very development. Keywords: mass media, socialization, valuable orientations, mass consciousness, manipulation, mass culture, information space.